A qualitative analysis of parent’s perceptions of available social support systems - Laura de la Roche; Nancie Im-Bolter (Discover Psychology)
Abstract Difficulties in social communication and interaction skills characteristic of autism are reported to play a critical role in high parenting stress. A widely acknowledged lack of effective supports make it more likely that parents of autistic children continue to experience increasingly greater levels of parenting stress over time. The current study aimed to further understand parent perceptions of social supports following their completion of a parent-implemented social skills intervention for their autistic child. Specifically, we explored additional supports beyond those targeting their child that parents of autistic children may perceive as necessary. We interviewed seven parents with autistic children to better understand their perception of the support systems available to, and utilized by, them. Inductive thematic analysis generated two primary themes: (1) parent’s emotions as leading of support needs and (2) support networks utilized or sought after by parents of autistic children. Our findings highlight the experiences and feelings of parents of autistic children regarding the support systems they perceive to be available and those they use and/or need. An understanding of parent experiences and perceived needs can be used to promote change, in particular, specific parent support following diagnosis and throughout the intervention process to encourage parent psychological well-being may be beneficial.